To What Extent Does Advertising Affect Brand Equity: The Food Industry - Cooke-Yarborough, Julie-Anna (2009)
The importance of brand equity to the success of businesses has become increasingly apparent in recent years, in particular as it is an incredibly powerful means of gaining competitive advantage. The significance of competitive advantage is especially noticeable in the food industry, where there is such vigorous competition among food firms to compete for success in the market. Resultantly, it is essential for these firms to create strong and unique brands that will appeal to a vast number of consumers.